Mananoligossacarídeos e β-glucanos em dietas de matrizes suínas em lactação - Oliveira, Maryane Sespere Faria de (2011)
An experiment was conducted in order to investigate the effect of inclusion of MOS and β-glucans in the diet of sows in late pregnancy and lactation on their body condition, reproductive performance and performance of piglets. There were 50 sows from same bloodline, multiparous, distributed in a completely randomized design with five treatments and ten replications, with one female per experimental unit. The experimental diets consisted of: control diet (without addition of additives), control diet with β-glucans (0.6 kg/ feed ton); control diet with the addition of MOS (1.5 kg/ feed ton); control diet with a combination of β-glucans (0.6 kg/ feed ton) and MOS (1.5 kg/ feed ton); control diet with added antibiotics (florfenicol-1.25 kg/ feed ton). Zootechnical performance parameters evaluated were feed intake, backfat thickness, weight loss and body condition of sows. The female reproductive performance was assessed by the number of piglets born alive, stillborn, mummified, weaned, mortality, weight gain, body weight of piglets at weaning and weaning to oestrus interval matrices. The inclusion of MOS, β-glucans and their association in comparison with antimicrobial additives and control diet did not affect body condition, reproductive performance of swine matrix and weight gain of piglets. However, females fed the diet with antimicrobial had a higher weaning to oetrus interval.